Rice-growers technical efficiency determinants in Benin: an Approach by Stochastic Border - ADEGNIKA, MOUTAÏROU; ADEGNIKA, MOUTAÏROU (My University, 2018)
For a few years, rice has been part of cereals the most consumed in Benin. This fact, its culture profits nowadays from a great political interest within the framework of the development of the sectors.This article aims to analyze the technical efficiency of rice-growers in the town of Glazoué. The results of the stochastic production border estimates overall show the inefficiency with an average efficiency index of 60.6% and 98.65231% of the differences at the border are related to the technical inefficiency of the producers. There is scope for increasing rice production in this municipality while keeping the level of inputs used inchanged. Furthermore, the distribution of efficiency indices shows that 46.67% of rice-growers recorded low technical efficiency scores between 0 and 50%. For any action to improve the technical efficiency of rice-growers, one must take into account variable such membership in a grouping, capital invested, labor and area planted that exercise a meaningful influence on the rice-growers technical efficiency.
Keywords: Glazoué; rice production; stochastic border; technical efficiency.